Designing broad-spectrum anti-HIV-1 gRNAs to target patient-derived variants. Issue 1 (December 2017) - Dampier, Will; Sullivan, Neil; Chung, Cheng-Han; Mell, Joshua; Nonnemacher, Michael; Wigdahl, Brian
Abstract Clustered regularly interspaced short palindromic repeats (CRISPR) CRISPR-associated protein 9 (Cas9), including specific guide RNAs (gRNAs), can excise integrated human immunodeficiency virus type 1 (HIV-1) provirus from host chromosomes. To date, anti-HIV-1 gRNAs have been designed to account for off-target activity, however, they seldom account for genetic variation in the HIV-1 genome within and between patients, which will be crucial for therapeutic application of this technology. This analysis tests the ability of published anti-HIV-1 gRNAs to cleave publicly available patient-derived HIV-1 sequences to inform gRNA design and provides basic computational tools to researchers in the field.